To the Problem of Relation between Personality Traits and Ethnic Stereotypes of Multinational University Students - I A Novikova; N N Panchekhina (Peoples' Friendship University of Russia (RUDN University), 2012)
The possibility of considering personality traits as factors of social perception determining the characteristics of ethnic stereotypes and prejudices is discussed in the article. The results of the empiric research of the relation of confidence and aggressiveness in the Russian students of a multinational university to the degree of their ethnic prejudices are presented.